Karakter Penciri Morfologi dan Tipe Panjatan Koleksi Tumbuhan Memanjat Annonaceae - Dewi Ayu Lestari; Linda Wige Ningrum (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the morphological characteristics and climbing types of selected climbing plants from the Annonaceae tribe, conserved ex-situ in the Purwodadi Botanical Gardens (KRP). The method used is observing the vegetative and generative organs of 12 types of qualitatively selected Annonaceae collections. Observational data were scored and analyzed in clusters to determine morphological characteristics and identify the type of climbing plants. The results showed that 2 clusters were referring to the Uvariae and Xylopiae tribes. The distinguishing morphological characteristics of the two clusters were the presence or absence of hooks and the presence or absence of feathers on the vegetative and generative organs. The types of climbing plants of Annonaceae KRP are hook-climbers and twiners. Conservation efforts that need to be done are to maintain and maintain the host of selected climbing plants from the Annonaceae KRP tribe, carry out regular monitoring and explore the potential of these species for environmental conservation education media. In conclusion, the morphological characteristics and types of climbing plants of Annonaceae can determine recommendations for ex-situ conservation efforts. Keywords: Annonaceae, Conservation, Morphology, Climbing Plants